Glass powder composite and method for producing glass powder composite
By using glass powder composites containing the first and second glass powders of different elements, the problem that traditional glasses are difficult to change the ion sustained release situation is solved, and the flexibility and effectiveness of ion sustained release over time is achieved.
Patent Information
- Application Number
- CN202380066797.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-12
- Filing Date
- 2023-10-05
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional ionic sustained-release glasses are difficult to change the sustained-release condition of ions over time.
Using a glass powder composite containing the first and second glass powders of different elements, the first glass powder is dissolved in the first period and the second glass powder is dissolved in the second period different from the first period.
The effect of changing the ion sustained release situation over time is achieved, and the ion sustained release flexibility of the glass powder complex is significantly improved.
Smart Images

Figure BDA0005315901120000161 
Figure BDA0005315901120000181 
Figure HDA0005315901130000011
Abstract
Description
Technical Field
[0001] The present invention relates to a glass powder composite and a method for producing the glass powder composite. Background Art
[0002] All along, the ion-slow-release glass of slow-release functional ions is known.For example, there is the technology (referring to patent documentation 1) that inorganic glass particles that can release phosphorus ions and calcium ions in water are used as granular soil improvement materials.In addition, there is the technology (patent documentation 2) that the antibacterial glass of the known silver ions with antibacterial effect of dissolving is used for resin moldings.In addition, in the medical applications such as bone repair materials and medical implants, there is the technology (patent documentation 3, patent documentation 4) of using bioglass.Moreover, there is the technology (referring to patent documentation 5) that ion-slow-release glass is used for deodorant compositions.
[0003] [Prior art literature]
[0004] [Patent Literature]
[0005] Patent Document 1: Japanese Patent Application Publication No. 2000-41482
[0006] Patent Document 2: Japanese Patent No. 6604499
[0007] Patent Document 3: Japanese Patent No. 6622416
[0008] Patent Document 4: Japanese Patent Application No. 2020-535881
[0009] Patent Document 5: International Publication No. 2019 / 189851 Summary of the invention
[0010] [Problems to be solved by the invention]
[0011] It is difficult for traditional ion-release glass to change the ion-release behavior over time.
[0012] An object of the present invention is to provide a glass powder composite that can change the ion sustained release condition over time.
[0013]
Methods to solve the problem
[0014] A glass powder composite according to one aspect of the present invention includes a first glass powder, which includes a first glass containing at least one element, and the first glass is dissolved during a first period; and a second glass powder, which includes a second glass containing at least one element different from the element of the first glass, and the second glass is dissolved during a second period different from the first period.
[0015] [Effects of the invention]
[0016] According to one aspect of the present invention, a glass powder composite can be provided that can change the ion sustained release profile over time. BRIEF DESCRIPTION OF THE DRAWINGS
[0017]
Figure 1
[0018]
Figure 2
[0019]
Figure 3
[0020]
Figure 4
[0021]
Figure 5
[0022]
Figure 6
[0023]
Figure 7
[0024]
Figure 8
[0025]
Fig. 9
[0026]
Fig.10
[0027]
Fig.11
[0028] Hereinafter, embodiments of the present invention will be described in detail.
[0029] <Glass powder composite>
[0030] The glass powder composite according to the present embodiment includes a first glass powder and a second glass powder. In the present specification, the glass powder composite refers to a material including at least two types of glass powders.
[0031] The first glass powder includes a first glass containing at least one element.
[0032] In this specification, "glass" includes not only amorphous substances but also crystalline substances, and also includes glass ceramics containing glass in part. Glass powder refers to powdered glass.
[0033] In addition, the size of the powder is preferably 0.01 μm to 100 μm, more preferably 0.1 μm to 50 μm, and further preferably 1 μm to 20 μm. In this specification, the particle size refers to the median particle size (D50) when the cumulative distribution of the volume basis measured by the laser diffraction / scattering method reaches 50%.
[0034] The first glass is not particularly limited, but is preferably phosphate glass. Phosphate glass contains phosphorus (P), and can be vitrified even with a composition having fewer network-forming components than silicate glass and borate glass. Therefore, phosphate glass can contain a variety of components in the glass, and these components are easily dissolved in water and gradually released in the form of ions (easy to release ions slowly or high ion slow release).
[0035] In this specification, the term "sustained ion release" refers to a property in which components contained in the glass powder are dissolved and gradually released in the form of ions.
[0036] Phosphate glass contains phosphorus pentoxide (P2O5). P2O5 plays a role in forming a network in the glass. In addition, due to the presence of P2O5, phosphate glass releases phosphate ions (PO4 3- ), which can impart the effect of preventing tooth remineralization and caries.
[0037] The content of P2O5 in the phosphate glass is preferably 40% by mass or more, more preferably 45% by mass or more, and further preferably 50% by mass or more. When the content of P2O5 in the phosphate glass is 40% by mass or more, it is easy to obtain glass.
[0038] In addition, there is no upper limit to the P2O5 content, but from the perspective of not making the melting temperature too high and being able to manufacture glass, it is preferably 90 mass % or less, more preferably 80 mass % or less, and further preferably 70 mass % or less.
[0039] The first glass preferably does not contain silicon dioxide (SiO2) at all. When containing SiO2, the content of SiO2 is preferably 5% by mass or less. By making the first glass completely free of SiO2 or having a content of SiO2 of 5% by mass or less, the reduction in the ion sustained release property in the first glass can be suppressed.
[0040] The first glass contains at least one element. The element contained in the first glass is an element that forms ions that are slowly released from the glass (hereinafter referred to as "slowly released ions").
[0041] The elements contained in the first glass include lithium (Li), calcium (Ca), strontium (Sr), barium (Ba), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), titanium (Ti), zirconium (Zr), tantalum (Ta), copper (Cu), silver (Ag), zinc (Zn), boron (B), gallium (Ga), tin (Sn), fluorine (F), etc. These elements may contain one or more. Among them, Li, Ca, Sr, Cu, Ag, Zn, B, Ga, and F are preferred.
[0042] Among these elements, Ca and Sr are preferred from the perspective of improving acid resistance by sustained-release ions, and Zn is preferred from the perspective of inhibiting acid generation. In addition, Ca, Zn, and F are preferred from the perspective of inhibiting tooth demineralization by sustained-release ions, and Ca and Sr are preferred from the perspective of promoting bone formation. In addition, Cu, Ag, Zn, B, Ga, and F are preferred from the perspective of antibacterial effects by sustained-release ions, and Li is preferred from the perspective of anti-inflammatory effects by sustained-release ions.
[0043] When the first glass contains Li, the content of Li in the first glass is not particularly limited, but is preferably 0% by mass to 30% by mass, more preferably 1% by mass to 25% by mass, and further preferably 5% by mass to 20% by mass, in terms of the amount converted into lithium oxide (Li2O). The inclusion of Li in the first glass can impart an anti-inflammatory effect, and the content of Li2O being 30% by mass or less can easily provide a glass that is not too soluble in water.
[0044] When the first glass contains Ca, the content of Ca in the first glass is not particularly limited, but is preferably 0% by mass to 25% by mass, more preferably 0.5% by mass to 10% by mass, and further preferably 1% by mass to 5% by mass, in terms of the amount converted into calcium oxide (CaO). The first glass contains Ca, which can impart an acid resistance effect, an effect of inhibiting tooth demineralization, and an effect of promoting bone formation, and the glass can be easily obtained by having a CaO content of 25% by mass or less.
[0045] When the first glass contains Sr, the content of Sr in the first glass is not particularly limited, but is preferably 0% by mass to 50% by mass, more preferably 10% by mass to 45% by mass, and further preferably 20% by mass to 40% by mass, in terms of the amount converted into strontium oxide (SrO). The first glass contains Sr, which can impart acid resistance and bone formation-promoting effects, and the SrO content is 50% by mass or less, so that the melting temperature of the glass is not too high, and the glass can be easily obtained.
[0046] When the first glass contains Cu, the content of Cu in the first glass is not particularly limited, but is preferably 0% by mass to 10% by mass, more preferably 0.01% by mass to 8% by mass, and further preferably 0.1% by mass to 5% by mass, in terms of the amount converted into copper oxide (CuO). The first glass contains Cu, which can impart an antibacterial effect, and the glass can be easily obtained by setting the content of CuO to 10% by mass or less.
[0047] When the first glass contains Ag, the content of Ag in the first glass is not particularly limited, but is preferably 0% by mass to 5% by mass, more preferably 0.01% by mass to 4% by mass, and further preferably 0.1% by mass to 3% by mass, in terms of the amount converted into silver oxide (Ag2O). The first glass contains Ag, which can impart an antibacterial effect, and the content of Ag2O is 5% by mass or less, making it easy to obtain glass.
[0048] When the first glass contains Zn, the content of Zn in the first glass is not particularly limited, but is preferably 0% by mass to 45% by mass, more preferably 1% by mass to 35% by mass, and further preferably 5% by mass to 30% by mass, in terms of the amount converted into zinc oxide (ZnO). When the first glass contains Zn, it is possible to impart an effect of inhibiting acid generation, an effect of inhibiting tooth demineralization, and an antibacterial effect, and when the content of ZnO is 45% by mass or less, it is easy to obtain glass.
[0049] When the first glass contains B, the content of B in the first glass is preferably 0 mass % to 10 mass % in terms of the amount converted into boron oxide (B2O3), more preferably 0.1 mass % to 9 mass %, and further preferably 1 mass % to 8 mass %. The inclusion of B in the first glass can impart an antibacterial effect, and the content of B2O3 being 10 mass % or less can suppress phase separation, making it easy to obtain glass.
[0050] When Ga is contained in the first glass, the content of Ga in the first glass is not particularly limited, but is preferably 0% by mass to 40% by mass, more preferably 0.1% by mass to 38% by mass, and further preferably 1% by mass to 35% by mass, in terms of the amount converted into gallium oxide (Ga2O3). The first glass contains Ga, which can impart an antibacterial effect, and the content of Ga2O3 is 40% by mass or less, making it easy to obtain glass.
[0051] When F is contained in the first glass, the content of F in the first glass is not particularly limited, but is preferably 0% by mass to 25% by mass, more preferably 0.1% by mass to 24% by mass, and further preferably 1% by mass to 22% by mass. When the first glass contains F, an effect of inhibiting tooth demineralization and an antibacterial effect can be imparted, and when the content of F is 25% by mass or less, glass can be easily obtained.
[0052] In the glass powder composite of the present embodiment, the first glass may contain sodium (Na), potassium (K), and aluminum (Al) as other elements unless the object of the present invention is impaired.
[0053] When the first glass contains Na, the content of Na in the first glass is not particularly limited, but is preferably 1% by mass to 40% by mass, more preferably 3% by mass to 35% by mass, and further preferably 5% by mass to 30% by mass, in terms of the amount converted into sodium oxide (Na2O). When the first glass contains Na, the melting temperature of the glass can be lowered, thereby improving the solubility of the glass. When the content of Na2O is 40% by mass or less, it is easy to obtain a glass that is not too soluble in water.
[0054] When K is contained in the first glass, the content of K in the first glass is not particularly limited, but is preferably 1% by mass to 40% by mass, more preferably 3% by mass to 35% by mass, and further preferably 5% by mass to 30% by mass, in terms of the amount converted into potassium oxide (K2O). When the first glass contains K, the melting temperature of the glass can be lowered, thereby improving the solubility of the glass. When the content of K2O is 40% by mass or less, it is easy to obtain a glass that is not too soluble in water.
[0055] When Al is contained in the first glass, the content of Al in the first glass is not particularly limited, but is preferably 0% by mass to 20% by mass, more preferably 0.5% by mass to 15% by mass, and further preferably 1% by mass to 10% by mass, in terms of the amount converted into aluminum oxide (Al2O3). The inclusion of Al in the first glass can improve the chemical durability of the first glass and enhance the stability as a glass, and the Al2O3 content is 20% by mass or less, so that the viscosity of the first glass can be adjusted.
[0056] The first glass powder dissolves the first glass during the first period. In this specification, "period" means a specified time. In addition, "glass dissolution" means that the glass dissolves in water and the elements contained in the glass are slowly released as ions.
[0057] The second glass powder includes a second glass containing at least one element.
[0058] The second glass is not particularly limited, but is preferably phosphate glass. As described above, phosphate glass contains phosphorus pentoxide (P2O5) which plays a role in forming a network in the glass.
[0059] In the second glass, the content of P2O5 in the phosphate glass is preferably 40% by mass or more, more preferably 45% by mass or more, and further preferably 50% by mass or more. Since the phosphate glass contains P2O5, the phosphate ions (PO4 3- ), which can impart the effect of preventing tooth remineralization and caries, and the glass can be easily obtained by making the content of P2O5 in the phosphate glass more than 40% by mass.
[0060] In addition, in the second glass, there is no upper limit on the P2O5 content, but from the perspective of not making the melting temperature too high and being able to manufacture glass, it is preferably 90 mass % or less, more preferably 80 mass % or less, and further preferably 70 mass % or less.
[0061] The second glass preferably does not contain silicon dioxide (SiO2) at all. When containing SiO2, the content of SiO2 is preferably 5% by mass or less. By the second glass not containing SiO2 at all or the content of SiO2 being 5% by mass or less, the reduction of the ion sustained release in the second glass can be suppressed.
[0062] The second glass contains at least one element different from the element of the first glass. The element contained in the second glass is an element that forms a slow-release ion.
[0063] In this specification, an element different from the element of the first glass means that at least one of the elements contained in the second glass is an element not contained in the first glass. For example, when the first glass contains zinc (Zn) but does not contain lithium (Li), it means that the second glass contains lithium (Li) and / or does not contain zinc (Zn).
[0064] The elements contained in the second glass are not particularly limited as long as they are different from the elements in the first glass, and examples thereof include Li, Ca, Sr, Ba, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ti, Zr, Ta, Cu, Ag, Zn, B, Ga, Sn, and F. One or more of these elements may be contained. Among them, Li, Ca, Sr, Cu, Ag, Zn, B, Ga, and F are preferred.
[0065] Among these elements, Ca and Sr are preferred from the perspective that the sustained-release ions can improve acid resistance, and Zn is preferred from the perspective of inhibiting acid generation. In addition, Ca, Zn, and F are preferred from the perspective that the sustained-release ions have an effect of inhibiting tooth demineralization, and Ca and Sr are preferred from the perspective of promoting bone formation. In addition, Cu, Ag, Zn, B, Ga, and F are preferred from the perspective that the sustained-release ions have an antibacterial effect, and Li is preferred from the perspective that the sustained-release ions have an anti-inflammatory effect.
[0066] When the second glass contains Li, the content of Li in the second glass is not particularly limited, but is preferably 0% by mass to 30% by mass, more preferably 1% by mass to 25% by mass, and further preferably 5% by mass to 20% by mass, in terms of the amount converted into lithium oxide (Li2O). When the first glass contains Li, an anti-inflammatory effect can be imparted, and when the content of Li2O is 30% by mass or less, it is easy to obtain a glass that is not too soluble in water.
[0067] When the second glass contains Ca, the content of Ca in the second glass is not particularly limited, but is preferably 0% by mass to 25% by mass, more preferably 0.5% by mass to 10% by mass, and further preferably 1% by mass to 5% by mass, in terms of the amount converted into calcium oxide (CaO). The inclusion of Ca in the second glass can impart an acid resistance effect, an effect of inhibiting tooth demineralization, and an effect of promoting bone formation, and the glass can be easily obtained by having a CaO content of 25% by mass or less.
[0068] When the second glass contains Sr, the content of Sr in the second glass is not particularly limited, but is preferably 0% by mass to 50% by mass, more preferably 10% by mass to 45% by mass, and further preferably 20% by mass to 40% by mass, in terms of the amount converted into strontium oxide (SrO). The inclusion of Sr in the second glass can impart acid resistance and bone formation promoting effects, and the SrO content is 50% by mass or less, so that the melting temperature of the glass is not too high, and the glass can be easily obtained.
[0069] When the second glass contains Cu, the content of Cu in the second glass is not particularly limited, but is preferably 0% by mass to 10% by mass, more preferably 0.01% by mass to 8% by mass, and further preferably 0.1% by mass to 5% by mass, in terms of the amount converted into copper oxide (CuO). The second glass contains Cu, which can impart an antibacterial effect, and the CuO content is 10% by mass or less, making it easy to obtain glass.
[0070] When the second glass contains Ag, the content of Ag in the second glass is not particularly limited, but is preferably 0% by mass to 5% by mass, more preferably 0.01% by mass to 4% by mass, and further preferably 0.1% by mass to 3% by mass, in terms of the amount converted into silver oxide (Ag2O). The second glass contains Ag, which can impart an antibacterial effect, and the content of Ag2O is 5% by mass or less, making it easy to obtain glass.
[0071] When the second glass contains Zn, the content of Zn in the second glass is not particularly limited, but is preferably 0% by mass to 45% by mass, more preferably 1% by mass to 35% by mass, and further preferably 5% by mass to 30% by mass, in terms of the amount converted into zinc oxide (ZnO). The inclusion of Zn in the second glass can impart an effect of inhibiting acid generation, an effect of inhibiting tooth demineralization, and an antibacterial effect, and the glass can be easily obtained by setting the content of ZnO to 45% by mass or less.
[0072] When the second glass contains B, the content of B in the second glass is preferably 0 mass % to 10 mass % in terms of the amount converted into boron oxide (B2O3), more preferably 0.1 mass % to 9 mass %, and further preferably 1 mass % to 8 mass %. The inclusion of B in the second glass can impart an antibacterial effect, and the content of B2O3 is 10 mass % or less, which inhibits phase separation and makes it easy to obtain glass.
[0073] When Ga is contained in the second glass, the content of Ga in the second glass is not particularly limited, but is preferably 0% by mass to 40% by mass, more preferably 0.1% by mass to 38% by mass, and further preferably 1% by mass to 35% by mass, in terms of the amount converted into gallium oxide (Ga2O3). The inclusion of Ga in the second glass can impart an antibacterial effect, and the content of Ga2O3 being 40% by mass or less can easily make it possible to obtain glass.
[0074] When the second glass contains F, the content of F in the second glass is not particularly limited, but is preferably 0% by mass or more and 25% by mass or less, more preferably 0.1% by mass or more and 24% by mass or less, and further preferably 1% by mass or more and 22% by mass or less. When the second glass contains F, an effect of inhibiting tooth demineralization and an antibacterial effect can be imparted, and when the content of F is 25% by mass or less, glass can be easily obtained.
[0075] In the glass powder composite of the present embodiment, the second glass may contain sodium (Na), potassium (K), and aluminum (Al) as other elements unless the object of the present invention is impaired.
[0076] When the second glass contains Na, the content of Na in the second glass is not particularly limited, but is preferably 1% by mass to 20% by mass, more preferably 3% by mass to 15% by mass, and further preferably 5% by mass to 10% by mass, in terms of the amount converted into sodium oxide (Na2O). When the second glass contains Na, the melting temperature of the glass can be lowered, thereby improving the solubility of the glass. When the content of Na2O is 20% by mass or less, it is easy to obtain a glass that is not too soluble in water.
[0077] When the second glass contains K, the content of K in the second glass is not particularly limited, but is preferably 1% by mass to 20% by mass, more preferably 3% by mass to 15% by mass, and further preferably 5% by mass to 10% by mass, in terms of the amount converted into potassium oxide (K2O). When the second glass contains Na, the melting temperature of the glass can be lowered, thereby improving the solubility of the glass. When the content of K2O is 20% by mass or less, it is easy to obtain a glass that is not too soluble in water.
[0078] When the second glass contains Al, the content of Al in the second glass is not particularly limited, but is preferably 0 mass % to 20 mass % in terms of the amount converted into aluminum oxide (Al2O3), more preferably 0.5 mass % to 15 mass %, and further preferably 1 mass % to 10 mass %. When the second glass contains Al, the chemical durability of the second glass can be improved and the stability as a glass can be increased, and when the content of Al2O3 is 20 mass % or less, the viscosity of the second glass can be adjusted.
[0079] The second glass powder dissolves the second glass in a second period different from the first period. In this specification, the second period different from the first period may be longer than the first period or shorter than the first period.
[0080] For example, when the second period is longer than the first period, the first glass in the first glass powder dissolves during the period of the second period overlapping the first period, and the second glass in the second glass powder dissolves. In addition, the second glass in the second glass powder dissolves during the period of the second period after the first period ends.
[0081] Specifically, when the first glass contains Zn and the second glass contains Li, during the first period, the first glass powder slowly releases Zn. 2+ , and the second glass powder will slowly release Li + During the second period, the second glass powder will slowly release Li + .
[0082] The difference between the residual rate of the first glass and the residual rate of the second glass is preferably 20% or more, more preferably 25% or more, and further preferably 30% or more. In this specification, the residual rate is also called the dissolution rate, which means the ratio of the mass of the undissolved glass after immersion to the mass of the glass before immersion when the glass is immersed in water, and is calculated according to the following formula:
[0083] Dissolution rate (%) = [(mass before immersion) - (mass after immersion)] × 100 / mass before immersion
[0084] The mass ratio of the first glass and the second glass mixed in the glass powder composite is not particularly limited, and is, for example, 10:1 to 1:10, preferably 7:1 to 1:7, and more preferably 5:1 to 1:5.
[0085] In the glass powder composite of this embodiment, at least one of the elements contained in the first glass may be the same as at least one of the elements contained in the second glass. For example, when the first glass contains zinc (Zn), the second glass may also contain zinc (Zn).
[0086] The dissolution rate is calculated by dissolving glass in acetic acid-sodium acetate buffer according to the following formula:
[0087] Dissolution rate (%) = [(weight before liquid immersion) - (weight after liquid immersion)] × 100 / weight before liquid immersion
[0088] The glass powder composite according to this embodiment may further include a third glass powder.
[0089] The third glass powder includes a third glass containing at least one element.
[0090] The third glass is not particularly limited, but is preferably phosphate glass. As described above, phosphate glass contains phosphorus pentoxide (P2O5) which plays a role in forming a network in the glass.
[0091] In the third glass, the content of P2O5 in the phosphate glass is preferably 40% by mass or more, more preferably 45% by mass or more, and further preferably 50% by mass or more. Since the phosphate glass contains P2O5, the phosphate ions (PO4 3- ), which can impart the effect of preventing tooth remineralization and caries, and the glass can be easily obtained by making the content of P2O5 in the phosphate glass more than 40% by mass.
[0092] In addition, in the third glass, there is no upper limit on the P2O5 content, but from the perspective of not making the melting temperature too high and thus enabling the manufacture of glass, it is preferably 90 mass % or less, more preferably 80 mass % or less, and further preferably 70 mass % or less.
[0093] The third glass preferably does not contain silicon dioxide (SiO2) at all. When containing SiO2, the content of SiO2 is preferably 5% by mass or less. By the third glass not containing SiO2 at all or the content of SiO2 being 5% by mass or less, the reduction of the ion sustained release property in the third glass can be suppressed.
[0094] The third glass contains at least one element different from the element of the first glass and the element of the second glass. The element contained in the third glass is an element that forms a slow-release ion.
[0095] In this specification, an element different from the element of the first glass and the element of the second glass means that at least one of the elements contained in the third glass is an element not contained in the first glass and the second glass. For example, if the first glass contains zinc (Zn) but does not contain strontium (Sr), and the second glass contains lithium (Li) but does not contain strontium (Sr), it means that the third glass contains strontium (Sr) but does not contain zinc (Zn) and lithium (Li).
[0096] The elements contained in the third glass are not particularly limited as long as they are different from the elements of the first glass and the elements of the second glass, and examples thereof include Li, Ca, Sr, Ba, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ti, Zr, Ta, Cu, Ag, Zn, B, Ga, Sn, and F. One or more of these elements may be contained. Among them, Li, Ca, Sr, Cu, Ag, Zn, B, Ga, and F are preferred.
[0097] Among these elements, Ca and Sr are preferred from the perspective that the sustained-release ions can improve acid resistance, and Zn is preferred from the perspective of inhibiting acid generation. In addition, Ca, Zn, and F are preferred from the perspective that the sustained-release ions have an effect of inhibiting tooth demineralization, and Ca and Sr are preferred from the perspective of promoting bone formation. In addition, Cu, Ag, Zn, B, Ga, and F are preferred from the perspective that the sustained-release ions have an antibacterial effect, and Li is preferred from the perspective that the sustained-release ions have an anti-inflammatory effect.
[0098] When the third glass contains Li, the content of Li in the third glass is not particularly limited, but is preferably 0% by mass to 30% by mass, more preferably 1% by mass to 25% by mass, and further preferably 5% by mass to 20% by mass, in terms of the amount converted into lithium oxide (Li2O). When the first glass contains Li, an anti-inflammatory effect can be imparted, and when the content of Li2O is 30% by mass or less, it is easy to obtain a glass that is not too soluble in water.
[0099] When the third glass contains Ca, the content of Ca in the third glass is not particularly limited, but is preferably 0% by mass to 25% by mass, more preferably 0.5% by mass to 10% by mass, and further preferably 1% by mass to 5% by mass, in terms of the amount converted into calcium oxide (CaO). The inclusion of Ca in the third glass can impart an acid resistance effect, an effect of inhibiting tooth demineralization, and an effect of promoting bone formation, and the glass can be easily obtained by having a CaO content of 25% by mass or less.
[0100] When the third glass contains Sr, the content of Sr in the third glass is not particularly limited, but is preferably 0% by mass to 50% by mass, more preferably 10% by mass to 45% by mass, and further preferably 20% by mass to 40% by mass, in terms of the amount converted into strontium oxide (SrO). The inclusion of Sr in the third glass can impart acid resistance and bone formation promoting effects, and the SrO content is 50% by mass or less, so that the melting temperature of the glass is not too high, and the glass can be easily obtained.
[0101] When the third glass contains Cu, the content of Cu in the third glass is not particularly limited, but is preferably 0% by mass to 10% by mass, more preferably 0.01% by mass to 8% by mass, and further preferably 0.1% by mass to 5% by mass, in terms of the amount converted into copper oxide (CuO). The inclusion of Cu in the third glass can impart an antibacterial effect, and the content of CuO is 10% by mass or less, making it easy to obtain glass.
[0102] When the third glass contains Ag, the content of Ag in the third glass is not particularly limited, but is preferably 0% by mass to 5% by mass, more preferably 0.01% by mass to 4% by mass, and further preferably 0.1% by mass to 3% by mass, in terms of the amount converted into silver oxide (Ag2O). The inclusion of Ag in the third glass can impart an antibacterial effect, and the content of Ag2O being 5% by mass or less makes it easy to obtain glass.
[0103] When the third glass contains Zn, the content of Zn in the third glass is not particularly limited, but is preferably 0% by mass to 45% by mass, more preferably 1% by mass to 35% by mass, and further preferably 5% by mass to 30% by mass, in terms of the amount converted into zinc oxide (ZnO). When the third glass contains Zn, it is possible to impart an effect of inhibiting acid generation, an effect of inhibiting tooth demineralization, and an antibacterial effect, and when the content of ZnO is 45% by mass or less, it is easy to obtain glass.
[0104] When the third glass contains B, the content of B in the third glass is preferably 0 mass % to 10 mass % in terms of the amount converted into boron oxide (B2O3), more preferably 0.1 mass % to 9 mass %, and further preferably 1 mass % to 8 mass %. The inclusion of B in the third glass can impart an antibacterial effect, and the content of B2O3 being 10 mass % or less can suppress phase separation, making it easy to obtain glass.
[0105] When Ga is contained in the third glass, the content of Ga in the third glass is not particularly limited, but is preferably 0% by mass to 40% by mass, more preferably 0.1% by mass to 38% by mass, and further preferably 1% by mass to 35% by mass, in terms of the amount converted into gallium oxide (Ga2O3). The inclusion of Ga in the third glass can impart an antibacterial effect, and the content of Ga2O3 being 40% by mass or less makes it easy to obtain glass.
[0106] When the third glass contains F, the content of F in the third glass is not particularly limited, but is preferably 0% by mass to 25% by mass, more preferably 0.1% by mass to 24% by mass, and further preferably 1% by mass to 22% by mass. When the third glass contains F, an effect of inhibiting tooth demineralization and an antibacterial effect can be imparted, and when the content of F is 25% by mass or less, glass can be easily obtained.
[0107] In the glass powder composite of the present embodiment, the third glass may contain sodium (Na), potassium (K), and aluminum (Al) as other elements unless the object of the present invention is impaired.
[0108] When the third glass contains Na, the content of Na in the third glass is not particularly limited, but is preferably 1% by mass to 20% by mass, more preferably 3% by mass to 15% by mass, and further preferably 5% by mass to 10% by mass, in terms of the amount converted into sodium oxide (Na2O). The inclusion of Na in the third glass can reduce the melting temperature of the glass and further improve the solubility of the glass. The content of Na2O being 20% by mass or less can easily provide a glass that is not too soluble in water.
[0109] When the third glass contains K, the content of K in the third glass is not particularly limited, but is preferably 1% by mass to 20% by mass, more preferably 3% by mass to 15% by mass, and further preferably 5% by mass to 10% by mass, in terms of the amount converted into potassium oxide (K2O). The inclusion of Na in the third glass can lower the melting temperature of the glass, thereby improving the solubility of the glass. The content of K2O is 20% by mass or less, so that a glass with a low solubility in water can be easily obtained.
[0110] When the third glass contains Al, the content of Al in the third glass is not particularly limited, but is preferably 0 mass % to 20 mass % in terms of the amount converted into aluminum oxide (Al2O3), more preferably 0.5 mass % to 15 mass %, and further preferably 1 mass % to 10 mass %. By containing Al in the third glass, the chemical durability of the third glass can be improved and the stability as a glass can be increased, and by the content of Al2O3 being 20 mass % or less, the viscosity of the third glass can be adjusted.
[0111] In the third glass powder, the third glass is dissolved in a third period different from the first period and the second period. In this specification, the third period different from the first period and the second period may be longer than the first period and the second period, or may be shorter than the first period and the second period.
[0112] For example, when the second period is longer than the first period, and the third period is longer than the second period, the first glass in the first glass powder is dissolved, the second glass in the second glass powder is dissolved, and the third glass in the third glass powder is dissolved during the period overlapping with the first period and the second period in the third period. In addition, during the period after the first period ends in the third period, the second glass in the second glass powder is dissolved, and the third glass in the third glass powder is dissolved. Furthermore, during the period after the second period ends in the third period, the third glass in the third glass powder is dissolved.
[0113] Specifically, when the first glass contains Zn, the second glass contains Li, and the third glass contains Sr, during the first period, the first glass powder slowly releases Zn. 2+, the second glass powder will slowly release Li + , and the third glass powder will slowly release Sr 2+ During the second period, the second glass powder will slowly release Li + , and the third glass powder will slowly release Sr 2+ During the third period, the third glass powder will slowly release Sr 2+ .
[0114] The difference between the residual rate of the second glass and the residual rate of the third glass is preferably 20% or more, more preferably 25% or more, and further preferably 30% or more.
[0115] In the glass powder composite of this embodiment, as described above, by including the first glass powder in which the first glass is dissolved in the first period and the second glass powder in which the second glass is dissolved in the second period different from the first period, the slow release of ions can be changed over time.
[0116] In the glass powder composite of the present embodiment, as described above, when the difference between the residual rate of the first glass and the residual rate of the second glass is 20% or more, the effect of changing the ion slow release with time is significant.
[0117] In the glass powder composite of the present embodiment, as described above, since the first glass and / or the second glass is phosphate glass, the ion-releasing property of the elements contained in the first glass and / or the second glass can be improved.
[0118] In the glass powder composite of the present embodiment, as described above, when the first glass and / or the second glass contains sodium (Na), the melting temperature of the glass can be lowered, and the solubility (ion sustained release) of the glass can be improved.
[0119] In the glass powder composite of the present embodiment, as described above, when the first glass and / or the second glass contains aluminum (Al), the chemical durability of the first glass and / or the second glass can be improved, thereby enhancing the stability as glass.
[0120] In the glass powder composite of the present embodiment, as described above, when the first glass or the second glass contains lithium (Li), an anti-inflammatory effect can be imparted.
[0121] In the glass powder composite of the present embodiment, as described above, when the first glass or the second glass contains zinc (Zn), it is possible to impart an effect of suppressing acid generation, an effect of suppressing tooth demineralization, and an antibacterial effect.
[0122] In the glass powder composite of the present embodiment, as described above, when the first glass or the second glass contains strontium (Sr), an acid resistance effect and a bone formation promoting effect can be imparted.
[0123] As described above, the glass powder composite of this embodiment further includes the third glass powder in which the third glass is dissolved in the third period different from the first period and the second period, thereby increasing the diversity of the effect of changing the ion slow release over time.
[0124] The use of the glass powder composite of this embodiment is not particularly limited. For example, it can be a resin, a coating, a soil modification material, etc. that exerts antibacterial properties over time. It can also be a bone filling material that can adapt to bone destruction or bone formation that changes over time, a dental material that can adapt to changes in oral lesions, etc.
[0125] As an example of the use of the glass powder composite, a dental composition when the glass powder composite of this embodiment is used as a dental material is described below. The dental composition involved in this embodiment contains the above-mentioned glass powder composite. In this specification, the dental composition means a composition used for dental materials.
[0126] Specifically, the glass powder composite for a dental composition includes a first glass powder, which includes a first glass containing at least one element, and the first glass is dissolved during a first period, and a second glass powder, which includes a second glass containing at least one element different from the element of the first glass, and the second glass is dissolved during a second period different from the first period.
[0127] For example, when the second period is longer than the first period, the first glass in the first glass powder will dissolve in the oral cavity during the period of the second period overlapping with the first period, and the second glass in the second glass powder will dissolve. In addition, during the period of the second period after the end of the first period, the second glass in the second glass powder will dissolve in the oral cavity.
[0128] Specifically, when the first glass contains Zn and the second glass contains Li, the first glass powder slowly releases Zn during the first period in the oral cavity. 2+ , and the second glass powder will slowly release Li + During the second period, the second glass powder will slowly release Li + .
[0129] In the glass powder composite used for the dental composition, the difference between the residual rate of the first glass and the residual rate of the second glass is preferably 20% or more, more preferably 25% or more, and even more preferably 30% or more.
[0130] In the dental composition of the present embodiment, by including the glass powder composite, the effect of the glass powder composite can be obtained. That is, the glass powder composite included in the dental composition includes the first glass powder dissolved from the first glass in the first period and the second glass powder dissolved from the second glass in the second period different from the first period, so that the sustained release of ions can be changed with the passage of time in the oral cavity.
[0131] Furthermore, in the dental composition of this embodiment, as described above, by including a glass powder composite in which the difference between the residual ratio of the first glass and the residual ratio of the second glass is 20% or more, the effect of changing the sustained release of ions over time in the oral cavity is remarkable.
[0132] It should be noted that the dental composition of the present embodiment may also contain other components in addition to the glass powder composite. There are no particular restrictions on other components in addition to the glass powder composite contained in the dental composition of the present embodiment, and for example, a polymer such as polyacrylic acid may be contained. The dental composition can constitute an ionomer cement by mixing such a glass powder composite with a polymer such as polyacrylic acid.
[0133] In addition, as long as the purpose of the present invention is not impaired, the dental composition of the present embodiment may contain, as other optional components, hardening accelerators such as hydrochlorides and sulfates, oily components such as hydrocarbons, higher fatty acids, and esters, various inorganic or organic colorants, antibacterial materials, fragrances, etc.
[0134] The dental composition of the present embodiment can be used for various dental materials. The use of the dental composition of the present embodiment is not particularly limited, and for example, there are dental cement, dental adhesive, dental temporary sealing material, dental temporary adhesive material, dental primer, dental coating agent, root surface covering material, dental composite resin, dental hard resin, dental cutting resin material, dental temporary restoration material, dental filling material, pulp capping material, bone filling material, bone cement, denture base material, artificial teeth, toothpaste, etc.
[0135] The method for manufacturing a glass powder composite according to the present embodiment is a method for substantially manufacturing the above-mentioned glass powder composite. Specifically, a first glass powder and a second glass powder are mixed, wherein the first glass powder includes a first glass containing at least one element, and the first glass is dissolved in a first period, and the second glass powder includes a second glass containing at least one element different from the element of the first glass, and the second glass is dissolved in a second period different from the first period.
[0136] In the step of mixing the first glass powder and the second glass powder in the manufacturing method of the glass powder composite according to the present embodiment, the first glass powder and the second glass powder contained in the above-mentioned glass powder composite are used. Therefore, the glass powder composite obtained by the manufacturing method according to the present embodiment can obtain the effect of the above-mentioned glass powder composite.
[0137] That is, the obtained glass powder composite is a glass powder composite, which includes a first glass powder, which includes a first glass containing at least one element, and the first glass is dissolved in a first period, and a second glass powder, which includes a second glass containing at least one element different from the element of the first glass, and the second glass is dissolved in a second period different from the first period, and the first glass powder and the second glass powder both have ion slow release properties, thus constituting a composite. Therefore, according to the manufacturing method involved in this embodiment, a glass powder composite can be obtained in which the ion slow release can be changed over time.
[0138] [Example]
[0139] The present invention will be further described below by way of examples. Various tests and evaluations were performed according to the following methods. In addition, in the following content, unitless values or "%" are based on mass unless otherwise specified.
[0140] <Preparation of Glass Powder>
[0141] Glass powder (glass 1 to 9) was prepared according to the composition shown in Table 1. First, the raw materials were weighed, mixed in a mortar for 10 minutes, placed in a platinum crucible, melted at 1100°C for 1 hour, and then the melt was cooled with an iron press. It was crushed with a ball mill for 30 minutes (ethanol wet crushing, 40 mm alumina balls, 100 rpm), and then crushed with a ball mill for another 30 minutes (ethanol wet crushing, 5 mm alumina balls, 100 rpm). Thereafter, the glass powder was recovered by centrifugal separation, and the residual ethanol was removed by reduced pressure drying (gauge pressure: -0.1 MPa, 40°C) to obtain glass powder (glass 1 to 9).
[0142]
Table 1
[0143]
[0144] <Composition of glass powder>
[0145] The compositions of the obtained glass powders (glasses 1 to 9) were confirmed. The glass powders (made of polyvinyl chloride in a ring shape) were analyzed using a fluorescent X-ray analyzer (ZSX Primus IV manufactured by RIGAKU) to determine the compositions of the glass powders. The results are shown in Table 1.
[0146] <Glass Powder Particle Size>
[0147] The particle size of the obtained glass powder (glass 1 to 9) was measured. The particle size of the glass powder is the median particle size (D50) when the cumulative distribution of the volume basis reaches 50% measured by the laser diffraction scattering method. The glass powder was dispersed in ethanol and measured using a laser diffraction scattering type particle size distribution analyzer (manufactured by Horiba, Partica (registered trademark) LA-960V2). It was confirmed that the D50 of all glass powders was 10±2μm.
[0148] <Glass Dissolution Rate>
[0149] 50 mg of glass powder was immersed in 10 mL of distilled water (pH 7), stored at 37°C, and then filtered with a 0.2 μm syringe filter. The filtered glass and the syringe filter were dried at 60°C for 48 hours. After that, the weight of the syringe filter and the glass was measured, and the amount of glass dissolved and the dissolution rate (residual rate) were calculated. The residual rate of the glass powder (glass 1 to 9) is as follows: Figure 1 And as shown in Table 1.
[0150] The glass dissolution rate is defined as the percentage of glass remaining after the glass powder composite is immersed in distilled water for one day. Based on this glass remaining rate, the dissolution rate of the glass powder constituting the glass powder composite is divided into the following three types (1) to (3).
[0151] (1) Fast: Residual rate is less than 5% (dissolves within a few hours)
[0152] (2) Normal: Residual rate is more than 5% and less than 60% (dissolved within a few days)
[0153] (3) Slow: Residual rate is more than 60% (dissolved within a few weeks)
[0154] <Solubility of Glass Powder Composite>
[0155] From Table 1, two or more glass powders were combined to prepare glass powder composites capable of dissolving one or more different ions in stages. The glass powder composites (Examples 1 to 5, Comparative Examples 1 to 5) formed by combining the glass powders in (1) to (3) above are shown in Table 2. The residual rates of the glass powder composites are shown in Table 2. Figure 2 to Figure 11 shown.
[0156]
Table 2
[0157]
[0158] As can be seen from Tables 1 and 2, a glass powder composite composed of two or more glass powders having different dissolution rates (difference in residual rate of 20% or more) can dissolve one or more different ions with a time difference (Examples 1 to 5).
[0159] On the other hand, it was found that a glass powder composite composed of two or more glass powders having similar dissolution rates (difference in dissolution rate less than 20%) could not dissolve one or more different ions with a time difference (Comparative Examples 1 to 5).
[0160] In summary, the first glass powder includes a first glass containing at least one element, and the first glass is dissolved during a first period. The second glass powder includes a second glass containing at least one element different from the element of the first glass, and the second glass is dissolved during a second period different from the first period. The glass powder composite including the above first glass powder and second glass powder can change the slow release of ions over time.
[0161] The embodiments disclosed above include, for example, the following aspects.
[0162] (Note 1)
[0163] A glass powder composite comprises a first glass powder and a second glass powder, wherein the first glass powder comprises a first glass containing at least one element, and the first glass is dissolved during a first period.
[0164] The second glass powder includes a second glass containing at least one element different from the element of the first glass, and the second glass is dissolved in a second period different from the first period.
[0165] (Note 2)
[0166] According to the glass powder composite described in Supplementary Note 1, the difference between the residual rate of the first glass and the residual rate of the second glass is 20% or more.
[0167] (Note 3)
[0168] The glass powder composite according to Supplementary Note 1 or 2, wherein the first glass and / or the second glass is phosphate glass.
[0169] (Note 4)
[0170] The glass powder composite according to any one of Appendixes 1 to 3, wherein the first glass and / or the second glass contains sodium.
[0171] (Note 5)
[0172] The glass powder composite according to any one of Appendixes 1 to 4, wherein the first glass and / or the second glass contains aluminum.
[0173] (Note 6)
[0174] The glass powder composite according to any one of Supplementary Notes 1 to 5, wherein the first glass or the second glass contains lithium.
[0175] (Note 7)
[0176] The glass powder composite according to any one of Supplementary Notes 1 to 6, wherein the first glass or the second glass contains zinc.
[0177] (Note 8)
[0178] The glass powder composite according to any one of Appendixes 1 to 7, wherein the first glass or the second glass contains strontium.
[0179] (Note 9)
[0180] The glass powder composite according to any one of the records in Notes 1 to 8 further includes a third glass powder, which includes a third glass containing at least one element different from the element of the first glass and the element of the second glass, and the third glass is dissolved in a third period different from the first period and the second period.
[0181] (Note 10)
[0182] A method for manufacturing a glass powder composite comprises mixing a first glass powder and a second glass powder,
[0183] The first glass powder includes a first glass containing at least one element, and the first glass is dissolved during a first period.
[0184] The second glass powder includes a second glass containing at least one element different from the element of the first glass, and the second glass is dissolved in a second period different from the first period.
[0185] Although the embodiments of the present invention have been described above, the present invention is not limited to the specific embodiments, and various modifications and changes can be made within the scope of the invention described in the claims.
[0186] This application claims priority based on Japanese Patent Application No. 2022-164278 filed on October 12, 2022, the entire contents of which are incorporated herein by reference.
Claims
1. A glass powder composite comprising a first glass powder and a second glass powder, The first glass powder includes a first glass containing at least one element, and the first glass is dissolved during a first period. The second glass powder includes a second glass containing at least one element different from the element of the first glass, and the second glass is eluted in a second period different from the first period. 2 . The glass powder composite according to claim 1 , wherein a difference between a residual rate of the first glass and a residual rate of the second glass is 20% or more. 3 . The glass powder composite according to claim 1 , wherein the first glass and / or the second glass is phosphate glass. 4 . The glass powder composite according to claim 1 , wherein the first glass and / or the second glass contains sodium. 5 . The glass powder composite according to claim 1 , wherein the first glass and / or the second glass contains aluminum. 6 . The glass powder composite according to claim 1 , wherein the first glass or the second glass contains lithium. 7 . The glass powder composite according to claim 1 , wherein the first glass or the second glass contains zinc. 8 . The glass powder composite according to claim 1 , wherein the first glass or the second glass contains strontium.
9. The glass powder composite according to claim 1 or 2 further comprises a third glass powder, wherein the third glass powder comprises a third glass containing at least one element different from the element of the first glass and the element of the second glass, and the third glass is dissolved in a third period different from the first period and the second period.
10. A method for producing a glass powder composite, comprising mixing a first glass powder and a second glass powder, The first glass powder includes a first glass containing at least one element, and the first glass is dissolved during a first period. The second glass powder includes a second glass containing at least one element different from the element of the first glass, and the second glass is eluted in a second period different from the first period.
Citation Information
Patent Citations
Substitute for peat-moss
JP2000041482A
Method for producing osteoconductive fibrous articles and medical implants comprising such osteoconductive fibrous articles
JP2020535881A
UV-ray irradiation device
JP2022164278A
Deodorant composition comprising ion sustained release glass
WO2019189851A1